Religious Educational Patterns of The Millennial Generation Trough Ngopi Senja Activities - Lestari, Chika Putri; Kurnianto, Rido; Syam, Aldo Redho; Arifin, Syamsul (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2024)
This study aims to describe the Islamic education strategy of the NDO community in Trenggalek Regency in shaping the religiosity of the millennial generation through Ngopi Senja and explore the implications of the activities of the NDO community in Trenggalek Regency on Islamic education and the religious attitudes of the millennial generation through Ngopi Senja. This study uses a case study approach with a qualitative method, namely collecting data through interviews with the committee and participants of the activity, direct observation of the Ngopi Senja activity, and documentation in the form of images and documents related to the focus of the research. The data analysis method in this study is based on the steps of Miles and Huberman, including data reduction, data presentation, and drawing conclusions to find the best results. The findings of this study include: 1) the Islamic education strategy used in the Ngopi Senja activity to shape the religiosity of the millennial generation is packaged through several stages, namely a) planning consists of formulating objectives, determining targets, themes, speakers, and facilities and infrastructure; b) implementation consists of the accuracy of the material with the target problems by utilizing digital technology; and c) evaluation of activities is carried out through comparison of target performance and monitoring through face-to-face and online; and 2) the implications of the activity strategies used by the NDO community in the Ngopi Senja activity have succeeded in shaping Islamic education and the religious attitudes of the millennial generation. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan strategi pendidikan Islam komunitas NDO Kabupaten Trenggalek dalam membentuk religiusitas generasi milenial melalui Ngopi Senja dan eksplorasi implikasi kegiatan komunitas NDO Kabupaten Trenggalek terhadap pendidikan Islam dan sikap religiusitas generasi milenial melalui Ngopi Senja. Penelitian ini menggunakan pendekatan studi kasus dengan metode kualitatif, yaitu mengumpulkan data melalui wawancara kepada panitia dan peserta kegiatan, pengamatan langsung terhadap kegiatan Ngopi Senja, dan dokumentasi berbentuk gambar dan dokumen terkait fokus penelitian. Metode analisis data dalam penelitian ini sesuai dengan langkah-langkah dari Miles dan Huberman, meliputi reduksi data, penyajian data, dan penarikan kesimpulan untuk mencari hasil yang terbaik. Temuan penelitian ini meliputi: 1) strategi pendidikan Islam yang digunakan dalam kegiatan Ngopi Senja untuk membentuk religiusitas generasi milenial dikemas melalui beberapa tahapan, yakni a) perencanaan terdiri dari merumuskan tujuan, menentukan sasaran, tema, pembicara, serta sarana dan prasarana; b) pelaksanaan terdiri dari ketepatan materi dengan problematika sasaran dengan memanfaatkan teknologi digital; dan c) evaluasi kegiatan dilakukan melalui perbandingan performa sasaran dan pemantauan melalui tatap muka dan daring; dan 2) implikasi dari strategi kegiatan yang digunakan komunitas NDO dalam kegiatan Ngopi Senja telah berhasil membentuk pendidikan Islam dan sikap religiusitas generasi milenial.